Detection of JunB and C-FLIP Psoriasis Genes Using the Reverse Transcriptase in-situ PCR Technique - Salleh, Mohd Nazil; RAMACHANDRAN, VASUDEVAN; Mulyadi Lai, Henkie Isahwan Ahmad; Ismail, Siti Aminah (Biomedical Sciences and Clinical Medicine, 2025)
Objective Psoriasis is a chronic skin disease and considered a multifactorial condition as it is caused by several risk factors; including genetic and environmental interactions. This study aimed to examine localization the expression of JunB and c-FLIP psoriasis genes at the mRNA cellular level using reverse transcriptase in-situ PCR (in-situ RT-PCR). Methods The in-situ RT-PCR technique was used to amplify the targeted mRNA from the formalin-fixed and paraffin-embedded tissues of three psoriasis patients. The localization of JunB and c-FLIP mRNA expression was achieved using in-situ RT-PCR along with the immunodetection technique. An immunohistochemistry profiler was used to count the pixels including the percentage contributions. Results Hematoxylin and eosin staining revealed the presence of parakeratosis, acanthosis, spongiosis and inflammatory cells. The staining analysis outcomes from in-situ RT-PCR and immunohistochemistry detection showed that the c-FLIP genes and JunB genes were significantly expressed in the surrounding nucleus area at the cellular level of the psoriasis tissue. JunB and c-FLIP mRNA scored positively in the the immunohistochemical analysis. Conclusions RT in-situ PCR can be a tool for identifying mRNA cellular gene expression. JunB and c-FLIP gene expression are significantly present in psoriasis.